KEBIJAKAN PERENCANAAN TATA RUANG DAN PEMBERDAYAAN POTENSI DAERAH DI INDONESIA - T. Yoyok Wahyu Subroto (Populasi, 2003)
The massive spatial expansion of the city into the fringe area has caused many problems mainly related to the spatial exploitation in both city and villages surrounding. The problem is also caused by the city development which its pace can not compete with the population growth. The aim of this study is to formulate the policy planning of spatial arrangement for the region potential empowerment. The spatial planning itself is directed to control and support in formulating spatial policy that should be efficient, effective and proportional. The descriptive method with field observation approach and literature survey is used to obtain the data. The result of the studypointed that the empowerment of the region power have to be supported by the spatial planning policy formulation which means that (1) spatial arrangement must put human and space in holistical point of view and bonding the social values together;(2) the urban-rural lingkages concept must put in a priority for formulating the internal spatial structure of regional planning and to empower villages as growth poles;(3) the spatial planning process has to be able to gain the best possibility of spatial arrangement where the pattern and distribution of space can ensure the existence of the city and village; (4) spatial planning have to accommodate spatial structure;(5) the application of spatial planning have to be based on self- containedpower of the region which put the bottom-up concept in a priority; (6) the spatial planning product have to be directed to the solid effort for future spatial usage.